Genetic variations in Toll-like receptor-4 and Myeloid differentiation protein-2 Genes among Giriraja and Indigenous Chicken - Ramesh, Sarathi N.; Ramakrishnappa, Nagaraja; Siddaraju, Naveen K.; Maheshwarappa, Yathish H.; Sringeshwaraiah, Nagaraja C. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study aimed to identify genetic polymorphism in chicken Toll-like receptor-4 (TLR4) and Myeloid differentiation protein-2 (MD-2) genes in Indigenous and Giriraja birds. Blood samples were collected from 50 each of indigenous and Giriraja birds and genomic DNA was isolated. Published primers were used to amplify chicken TLR4 (exon 3) and MD-2 (exon 1) genes. The polymorphism was determined in TLR4 and MD-2 genes using RFLP analysis employing TaqI and AseI restriction enzymes, respectively. RFLP analysis of TLR4 gene revealed a monomorphic pattern both in Indigenous and Giriraja birds. Whereas RFLP analysis of MD-2 gene in both Indigenous and Giriraja birds showed polymorphic patterns. In indigenous birds, genotypic frequencies were 0.02, 0.14, and 0.84 for AA, AB, and BB, respectively, and gene frequencies were 0.09 and 0.91 for alleles A and B. In Giriraja birds, genotypic frequencies were 0.02, 0.46, and 0.52 for AA, AB, and BB, respectively, and gene frequencies were 0.25 and 0.75 for alleles A and B. Sequence Alignment of A and B alleles of MD-2 gene showed a SNP (G → A) at nucleotide position 73 bp in B allele.